Reversal in Solvatochromism, enol-imine/keto-amine Tautomerism and (E)-(Z) Photoisomerizations in a Benzylidene Aniline Schiff Base Derivative in Different Solvents - Sidir, Isa; Sidir, Yadigar Guelseven; Berber, Halil; Ramos, Maria L.; Justino, Licinia L. G.; FAUSTO, RUI (MDPI, 2025)
A novel Schiff base, (E)-4-acetyl-N-(4-hydroxy-3-methoxybenzylidene)aniline (abbreviated as ANHMA), was synthesized and characterized using infrared and H-1- and C-13-NMR spectroscopies. Optical properties in different solvents were evaluated using UV-vis absorption spectroscopy. The compound is shown to exhibit both positive and negative solvatochromism with reversal occurring for solvents with E-T(30)similar to 45 (e.g., DMSO). The solvatochromic behavior of the compound was found to be strongly dependent on the hydrogen bond abilities and polarizability of the solvent, the observed reversal in solvatochromism being explained by the change in the dominant solvent effects in non-polar and polar-aprotic solvents (H-bond acceptor ability of the solvent and polarizability) compared to polar-protic solvents (H-bond donor ability), according to the developed Catal & aacute;n multiparametric solvatochromic model. In all freshly prepared solutions studied, the (E)-enol-imine tautomer of the compound was found to strongly predominate over the keto-amine tautomeric forms, the latter increasing their populations over time in the presence of H-bond donor/acceptor species. Irradiation of ANHMA with UV light (lambda >= 311 nm) was also investigated in several solvents and shown to follow a general pattern, with the conversion of the (E)-enol-imine tautomer into the keto-amine forms in a solvent-mediated enol-imine/keto-amine tautomerism, and (Z)->(E) C=C isomerization between the keto-imine forms. The experimental results received support from an extensive series of calculations on the structure and UV-vis spectra of the relevant tautomeric/isomeric forms of the compound performed at the DFT(B3LYP)/6-311++G(d,p) level of approximation (including time-dependent DFT calculations and solvent consideration).
Keywords: Benzylidene Aniline Schiff Base-type Imine Dye; Hydrogen Bonding; Isomerism; Solvatochromism; Tautomerism